(untitled) (Scientific journal of the Fergana State University, 2024)
This article describes theoretical concepts about colors and describes the role and influence of colours that are an integral part of the material world in cognitive linguistics. The colorinim study was approached lexically-semantically, grammatically, and cognitively in the paper.